Code Mixing in Karonese and Indonesian: Sociolinguistics Study: Array - Sembiring, Annisa Putri (Universitas Harapan Medan, 2022)
The objective of this research is to find out the types of code mixing and the reason why the sellers and buyers use code mixing in speaking. It was conducted by using qualitative methodology. The population of this research was the sellers of Simalingkar traditional market with consisted of three sellers. The instrument for collecting the data was recording. The data analysis could be concluded that the types of code mixing in this research were insertion of word, insertion of phrase and insertion of sentence. Meanwhile, the frequency of the data in this research were the insertion of word was 19,56%, the insertion of phrase was 34,78% and the insertion of sentence was 45,65%.